2016
DOI: 10.1002/prot.25155
|View full text |Cite
|
Sign up to set email alerts
|

TMSEG: Novel prediction of transmembrane helices

Abstract: Transmembrane proteins (TMPs) are important drug targets because they are essential for signaling, regulation, and transport. Despite important breakthroughs, experimental structure determination remains challenging for TMPs. Various methods have bridged the gap by predicting transmembrane helices (TMHs), but room for improvement remains. Here, we present TMSEG, a novel method identifying TMPs and accurately predicting their TMHs and their topology. The method combines machine learning with empirical filters. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 46 publications
3
44
0
Order By: Relevance
“…This analysis revealed that the previously developed servers are not completely adequate for membrane proteins, which emphasizes the importance of developing specialized tools to discriminate mutations for different topological regions of membrane proteins. The topology information can be obtained from the available structure prediction tools such as TMHMM, MemBrain, TMSeg, MemConP etc.…”
Section: Resultsmentioning
confidence: 99%
“…This analysis revealed that the previously developed servers are not completely adequate for membrane proteins, which emphasizes the importance of developing specialized tools to discriminate mutations for different topological regions of membrane proteins. The topology information can be obtained from the available structure prediction tools such as TMHMM, MemBrain, TMSeg, MemConP etc.…”
Section: Resultsmentioning
confidence: 99%
“…We used bioinformatics tools that searched for similarities between Babo1 and verified transmembrane proteins, utilized algorithms that were trained on transmembrane protein datasets, and also analyzed Babo1 only based on its sequence of amino acid residues. The battery of applied programs included TMSEG (Bernhofer et al , ), PolyPhobius (Käll et al , ; Käll et al , ), Phobius (Käll et al , ; Käll et al , ), MEMSAT3 (Jones et al , ), MEMSAT‐SVM (Nugent and Jones, ), PHDhtm (Rost et al , ; Combet et al , ), TMHMM (Krogh et al , ), TMpred (Hofmann and Stoffel, ), DAS‐TMfilter (Cserzo et al , ), MINNOU (Cao et al , ), TBBpred (Natt et al , ), PRED‐TMR2 (Pasquier and Hamodrakas, ), and the Kyte and Doolittle hydrophobicity plot (Kyte and Doolittle, ). However, no transmembrane spanning segments have been identified and all of these programs predicted that Babo1 is not a transmembrane protein.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of per-family view even more misleading is the number of 49% of all human protein families associated with the plasma membrane ( Fig. S1) when fewer than 25% of all human proteins have a membrane helix, and only 13% have more than one transmembrane helix [21]. Thus, we apparently cannot estimate the spectrum of localizations for an organism from experimental and homology-inferred annotations alone.…”
Section: Localization Reliably Inferred For 81% Of the Human Protein mentioning
confidence: 96%